2021
DOI: 10.1039/d1nj02469h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of model bacteriochlorophylls containing substituents of native rings A, C and E

Abstract: An established route to the bacteriochlorophyll skeleton from two dihydrodipyrrin halves has been extended to accommodate several substituents characteristic of the native bacteriochlorophyll a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(55 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…The FTIR spectra of F1 and F2 demonstrated that the peaks for both formulations were not detected for both C=C stretching and C=O stretching and shifted for N-H stretching to 3675 and 3672 cm −1 , respectively. This suggests that cholesterol is the difference in composition between F1 and F2 [40,41]. Additionally, the peak of N-H stretching in MPa was slightly shifted when comparing F1 with F2.…”
Section: Ftir-atr Spectroscopymentioning
confidence: 93%
See 1 more Smart Citation
“…The FTIR spectra of F1 and F2 demonstrated that the peaks for both formulations were not detected for both C=C stretching and C=O stretching and shifted for N-H stretching to 3675 and 3672 cm −1 , respectively. This suggests that cholesterol is the difference in composition between F1 and F2 [40,41]. Additionally, the peak of N-H stretching in MPa was slightly shifted when comparing F1 with F2.…”
Section: Ftir-atr Spectroscopymentioning
confidence: 93%
“…Additionally, the peak of N-H stretching in MPa was slightly shifted when comparing F1 with F2. Therefore, the H of N-H stretching in MPa forms a weak H-bond (hydrogen bond) with the hydroxyl group in cholesterol [40,41].…”
Section: Ftir-atr Spectroscopymentioning
confidence: 99%
“…2). While 1 H NMR spectroscopic analysis routinely affords a characteristic ABX pattern of the methylene protons on the carbon adjacent to the stereogenic center, structural analysis of such pyrrole–nitrohexanones has previously been reported for only four compounds, 46–48 although compounds containing the 2-(2-nitroethyl)pyrrole moiety are growing in importance. 49…”
Section: Resultsmentioning
confidence: 99%
“…2). While 1 H NMR spectroscopic analysis routinely affords a characteristic ABX pattern of the methylene protons on the carbon adjacent to the stereogenic center, structural analysis of such pyrrole-nitrohexanones has previously been reported for only four compounds, [46][47][48] although compounds containing the 2-(2-nitroethyl)pyrrole moiety are growing in importance. 49 To our surprise, the standard self-condensation conditions 15 afforded 5-unsubstituted BC-1 only in 4.1% yield and was accompanied by 5-methoxybacteriochlorin BC-2 in 1.7% yield.…”
Section: Bacteriochlorin Synthesis -Reconnaissancementioning
confidence: 99%
“…Their stereochemistry was determined by Ian Fleming, by Burrell et al and by Crabbé et al (reviewed in Brockmann, [ 16 ]). Total syntheses were achieved by the groups of Strell [ 17 ] and, more rigorously, Woodward [ 18 ], but a general synthetic access of Chl-type pigments remains a challenge [ 19 , 20 ].…”
mentioning
confidence: 99%